Compact 1 × 2 and 2 × 2 Dual Polarized Series-Fed Antenna Array for X-Band Airborne Synthetic Aperture Radar Applications - Venkata Kishore Kothapudi; Vijay Kumar (Journal of the Korean Institute of Electromagnetic Engineering and Science, 2018)
In this paper, compact linear dual polarized series-fed 1 × 2 linear and 2 × 2 planar arrays antennas for airborne SAR applications are proposed. The proposed antenna design consists of a square radiating patch that is placed on top of the substrate, a quarter wave transformer and 50-Ω matched transformer. Matching between a radiating patch and the 50-Ω microstrip line is accomplished through a direct coupled-feed technique with the help of an impedance inverter (λ/4 impedance transformer) placed at both horizontal and vertical planes, in the case of the 2 × 2 planar array. The overall size for the prototype-1 and prototype-2 fabricated antennas are 1.9305 × 0.9652 × 0.05106 λ03 and 1.9305 × 1.9305 × 0.05106 λ03, respectively. The fabricated structure has been tested, and the experimental results are similar to the simulated ones. The CST MWS simulated and vector network analyzer measured reflection coefficient (S11) results were compared, and they indicate that the proposed antenna prototype-1 yields the impedance bandwidth > 140 MHz (9.56–9.72 GHz) defined by S11 < −10 dB with 1.43%, and S21 < −25 dB in the case of prototype-2 (9.58–9.74 GHz, S11 < −10 dB) > 140 MHz for all the individual ports. The surface currents and the E- and H-field distributions were studied for a better understanding of the polarization mechanism. The measured results of the proposed dual polarized antenna were in accordance with the simulated analysis and showed good performance of the S-parameters and radiation patterns (co-pol and cross-pol), gain, efficiency, front-to-back ratio, half-power beam width) at the resonant frequency. With these features and its compact size, the proposed antenna will be suitable for X-band airborne synthetic aperture radar applications.